Municipal administration and corruption in the implementation of federal educational programs - Olivieri, Cecília (2018)
This paper analyzes the implementation of federal education programs in municipalities through structured analysis of the texts in supervision reports provided by the Comptroller General of Brazil for the year 2014. The aim is to analyze the problems affecting the management of federal programs in municipalities. Studies on management and corruption in municipalities were reviewed and form the theoretical framework. The main conclusion is that it is necessary to increase the attention of researchers and managers to issues related to the quality of municipal management, because problems in program implementation is more likely to be the result of bad management than corruption.